2013
DOI: 10.1111/hpb.12019
|View full text |Cite
|
Sign up to set email alerts
|

Redefining the R1 resection for pancreatic ductal adenocarcinoma: tumour lymph nodal burden and lymph node ratio are the only prognostic factors associated with survival

Abstract: LNB and LNR are the only prognostic factors for CSS in patients with pancreatic head adenocarcinoma, but do not predict recurrence. Microscopic RMs does not seem to influence the outcome even when redefined. Further prospective studies are indicated to substantiate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 38 publications
2
39
1
Order By: Relevance
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] There were 5 prospective studies, 1 randomised controlled trial and 13 retrospective studies (Table 1). All included studies analysed survival using the Kaplan-Meier method, defining an event as the death of a patient and overall survival from the time elapsed from surgery to death.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] There were 5 prospective studies, 1 randomised controlled trial and 13 retrospective studies (Table 1). All included studies analysed survival using the Kaplan-Meier method, defining an event as the death of a patient and overall survival from the time elapsed from surgery to death.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Association between these subgroups and overall survival was investigated and presented using Kaplan-Meier curves. A high lymph node ratio was associated with decreased overall survival in 17 studies, [13][14][15][16][17][18][19][20][21][22][24][25][26][27][28]30,31 and no association was found in two studies. 23,29 Lymph node ratio was significantly associated with overall survival in most studies.…”
Section: Lymph Node Ratio Association With Overall Survivalmentioning
confidence: 99%
See 2 more Smart Citations
“…Median survival was 15 months (9-23 months) and the authors concluded that in high-volume centers, vascular resection has acceptable morbidity, mortality and survival outcomes and should not be seen as a contraindication to curative surgery. By pooling results from studies reporting resection margin status after PD [8,18,[36][37][38][39][40][41], a positive medial resection margin was reported in 38.2% of 701 patients. However, following PD with PV/SMV resection, the medial resection margin is only positive in 16% of patients, and it is well recognized that an R0 medial resection margin is a predictor of improved survival [8].…”
Section: Pv Resection In Pdmentioning
confidence: 99%